Phase 1 Study of Molibresib (GSK525762), a Bromodomain and Extra-Terminal Domain Protein Inhibitor, in NUT Carcinoma and Other Solid Tumors. Issue 2 (6th November 2019) - Piha-Paul, Sarina A; Hann, Christine L; French, Christopher A; Cousin, Sophie; Braña, Irene; Cassier, Phillippe A; Moreno, Victor; de Bono, Johann S; Harward, Sara Duckworth; Ferron-Brady, Geraldine; Barbash, Olena; Wyce, Anastasia; et al.
Abstract: Background: Bromodomain and extra-terminal domain proteins are promising epigenetic anticancer drug targets. This first-in-human study evaluated the safety, recommended phase II dose, pharmacokinetics, pharmacodynamics, and preliminary antitumor activity of the bromodomain and extra-terminal domain inhibitor molibresib (GSK525762) in patients with nuclear protein in testis (NUT) carcinoma (NC) and other solid tumors. Methods: This was a phase I and II, open-label, dose-escalation study. Molibresib was administered orally once daily. Single-patient dose escalation (from 2 mg/d) was conducted until the first instance of grade 2 or higher drug-related toxicity, followed by a 3 + 3 design. Pharmacokinetic parameters were obtained during weeks 1 and 3. Circulating monocyte chemoattractant protein-1 levels were measured as a pharmacodynamic biomarker. Results: Sixty-five patients received molibresib. During dose escalation, 11% experienced dose-limiting toxicities, including six instances of grade 4 thrombocytopenia, all with molibresib 60–100 mg. The most frequent treatment-related adverse events of any grade were thrombocytopenia (51%) and gastrointestinal events, including nausea, vomiting, diarrhea, decreased appetite, and dysgeusia (22%–42%), anemia (22%), and fatigue (20%). Molibresib demonstrated an acceptable safety profile up to 100 mg; 80 mg once daily was selected as the recommended phase II dose. Following single and repeat dosing, molibresib showed rapid absorption and elimination (maximum plasma concentration: 2 hours; t1/2 : 3–7 hours). Dose-dependent reductions in circulating monocyte chemoattractant protein-1 levels were observed. Among 19 patients with NC, four achieved either confirmed or unconfirmed partial response, eight had stable disease as best response, and four were progression-free for more than 6 months. Conclusions: Once-daily molibresib was tolerated at doses demonstrating target engagement. Preliminary data indicate proof-of-concept in NC.